The consciousness of virtue: uncovering the gaps between educational specialists and the general public in their understanding of virtue in Japan - Tachibana, Koji; Nakazawa, Eisuke (Frontiers in Psychology, 2024)
Virtue is a normative concept that constitutes social and moral codes. The notion of virtue can be identified in both the West and the East. Since this concept was revived in academia in the 20th century after a long sinking into oblivion, contemporary professional researchers, but not the general public, may be familiar with this notion. We conducted a survey on the attitudes of educational specialists and the general public regarding the notion of virtue in Japan. Our study found that, in contrast to educational specialists, the general public were not so familiar with the notion; both had a positive image of virtue and a poor understanding of the Confucian notions of virtue; both retain Buddhist values under the term of virtue, but educational specialists tended to associate ancient Greek and Western elements with the notion of virtue. Educational specialists emphasized active, intellectual virtues, such as practical wisdom, whereas the general public emphasized passive, emotional virtues, such as gratitude. Our study showed that, the notion of virtue was understood in different ways between educational specialists and the general public in Japan. This finding has several social implications, such as academic integrity and educational policy.